Law, Culture and Visual Studies
XLI, 1042 p. 125 illus., 65 illus. in color.
Keywords: The proposed volumes are aimed at a multidisciplinary audience and seek to fill the gap between law, semiotics and visuality providing a comprehensive theoretical and analytical overview of legal visual semiotics. They seek to promote an interdisciplinary debate from law, semiotics and visuality bringing together the cumulative research traditions of these related areas as a prelude to identifying fertile avenues for research going forward. Advance Praise for Law, Culture and Visual Studies This diverse and exhilarating collection of essays explores the many facets both historical and contemporary of visual culture in the law. It opens a window onto the substantive, jurisdictional, disciplinary and methodological diversity of current research. It is a cornucopia of materials that will enliven legal studies for those new to the field as well as for established scholars. It is a ‘must read’ that will leave you wondering about the validity of the long held obsession that reduces the law and legal studies to little more than a preoccupation with the word. Leslie J Moran Professor of Law, Birkbeck College, University of London Law, Culture & Visual Studies is a treasure trove of insights on the entwined roles of legality and visuality. From multiple interdisciplinary perspectives by scholars from around the world, these pieces reflect the fullness and complexities of our visual encounters with law and culture. From pictures to places to postage stamps, from forensics to film to folklore, this anthology is an exciting journey through the fertile field of law and visual culture as well as a testament that the field has come of age. Naomi Mezey, Professor of Law, Georgetown University Law Center, Washington, D.C., USA This highly interdisciplinary reference work brings together diverse fields including cultural studies, communication theory, rhetoric, lawand film studies, legal and social history, visual and legal theory, in order to document the various historical, cultural, representational and theoretical links that bind together law and the visual. This book offers a breath-taking range of resources from both well-established and newer scholars who together cover the field of law’s representation in, interrogation of, and dialogue with forms of visual rhetoric, practice, and discourse. Taken together this scholarship presents state of the art research into an important and developing dimension of contemporary legal and cultural inquiry. Above all, Law Culture and Visual Studies lays the groundwork for rethinking the nature of law in our densely visual culture: How are legal meanings produced, encoded, distributed, and decoded? What critical and hermeneutic skills, new or old, familiar or unfamiliar, will be needed? Topical, diverse, and enlivening, Law Culture and Visual Studies is a vital research tool and an urgent invitation to further critical thinking in the areas so well laid out in this collection. Desmond Manderson, Future Fellow, ANU College of Law / Research School of Humanities & the Arts, Australian National University, Australia.